Featuring writing skills of three, four and five-year-old preschool children - Sanchez, R. D. (2003)
The descriptive study of early writing attempts of 36 three to five year old preschool children was conducted using four writing event sessions. Using the Early Writing Attempts Checklist of Medrano, each child's featural writing skill was scored. Results revealed that 34% of children, all three years old, were in the idiographic stage, 31%, mostly four years old, were in the symbolic stage, 28%, mostly five years old, were in invented spelling stage and 8%, all five years old, were in the conventional writing stage. Findings of this study highlight the importance of looking into early writing attempts as significant precursors to writing development and may also serve as basis in redirecting preschools' writing programs and writing assessment tools.
Keywords: Child writing